The Relation Between Visual Impairment and Extremity Fractures - Berrak Şekeryapan; Mehmet Sabri Balık; Veysi Öner; Yılmaz Güvercin; Kemal Türkyılmaz; Adem Erkut; Mustafa Durmuş (Türk Oftalmoloji Dergisi, 2013)
Purpose: To evaluate the association between the development of extremity fracture and visual impairment in adults. Material and Method: This study included 56 patients (patient group) aged 18 years or older who had extremity fractures due to a fall. The control group (n=42) was selected from visitors who had regular medical check-ups at our hospital. Each participant underwent a full ophthalmologic examination. Mean age was compared by Student’s t test. The other variables were compared by chi-square test. Results: The prevalence of subjects with visual impairment was significantly higher in the patients group (78.6%) than in the control group (38.1%) (p<0.05). The prevalence of treatable eye diseases such as cataract and refractive errors were significantly higher in the patient group than in the control group (p<0.05 for both). Twenty-eight patients (50%) in the patient group and 8 subjects in the control group had visual acuities lower than 0.5 (p<0.05). Discussion: We have found that the prevalence of visual impairment was significantly higher in adults with extremity fractures due to falls than in the control group. Hence, we believe that regular ophthalmological examination in adults, providing regular use of eyeglasses in patients with refractive errors, and timely treatment of treatable eye diseases such as cataract could decrease the extremity fractures from falls in adults. (Turk J Ophthalmol 2013; 43: 250-2)